Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.21037/tlcr-21-959
|View full text |Cite
|
Sign up to set email alerts
|

A standard for hilar and intrapulmonary lymph node dissection and pathological examination in early non-small cell lung cancer

Abstract: Background: There is considerable variation in the staging of lymph nodes (LNs) as part of tumor, node, metastasis (TNM) staging of non-small cell lung cancer (NSCLC). A new dissection and pathological examination standard for hilar and intrapulmonary LNs needs to be established for patients with early-stage T1-3N0M0 NSCLC.Methods: This study involved 3,002 patients with T1-3N0M0 NSCLC who underwent radical lobectomy or total pneumonectomy in the thoracic departments of 11 Chinese institutions between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
(27 reference statements)
2
6
0
Order By: Relevance
“…For T1 lung cancer, only one patient (1/169, 0.60%) had lymphatic metastasis at station 9 [ 25 ]. In addition, compared to mediastinal and hilar nodes, less attention was afforded to intrapulmonary lymph nodes (station 12, 13, 14) [ 26 ]. However, intrapulmonary lymph nodes had a relatively higher metastasis risk [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For T1 lung cancer, only one patient (1/169, 0.60%) had lymphatic metastasis at station 9 [ 25 ]. In addition, compared to mediastinal and hilar nodes, less attention was afforded to intrapulmonary lymph nodes (station 12, 13, 14) [ 26 ]. However, intrapulmonary lymph nodes had a relatively higher metastasis risk [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this large population study, six variables including age, sex, laterality, histological classification, pathological T stage, and HI Standard were reviewed [ 10 ]. We identified that five of six factors, except laterality, were correlated with OS in univariate and multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological characteristics included histological classification from the the International Statistical Classification of Diseases and Related Health Problems 10th Revision (Squamous cell carcinoma, Adenocarcinoma, Adenosquamous carcinoma, Others), and pathological T stage from the eighth edition of the AJCC/UICC TNM staging (T1, T2, T3). The HI Standard [ 9 , 10 ] was defined as recommendation of at least 10 examined lymph nodes, which included at least one station in 10, 11 lymph node and one station in 12, 13, 14 lymph node. Lymph nodes were either dissected in surgical resection or re-sampled by the surgeon after surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, for patients undergoing a PN, strict staging should be performed before surgery, and methods such as PET-CT should be used to assess lymph node metastasis. In addition, the greater the number of lymph nodes dissected, the longer the OS may be; this is representative of the real-world situation ( 27 ). For patients with persistent hemoptysis, medical and interventional therapy are ineffective; or when intraoperative lobectomy and sleeve resection fail in patients with preoperative neoadjuvant therapy, PN is also required for lymph node advanced.…”
Section: Discussionmentioning
confidence: 99%